University Faculty Perception of Cyber-Plagiarism: A Virtual Discussion Group - Gallent Torres, Cinta (2021)
This study explores academic cyberplagiarism from the perspective of undergraduate instructors for the Translation and Interpretation major at the International University of Valencia, Spain. Since cyberplagiarism has become increasingly widespread by university students, instructors must reflect on ways to deter students from using this fraudulent practice as a structural and educational resource. A qualitative methodology was used based on a virtual discussion group among participating faculty (n=16) who responded to a script that consisted of six questions designed to learn (i) how instructors tackle cyberplagiarism through a virtual teaching framework; (ii) their role and responsibility upon encountering a case of plagiarism among their students, and (iii) who is responsible for quantifying the gravity of these actions. The study also considers actions taken by the institution and the support it provides its faculty to address this practice and also established a guideline to standardized criteria among faculty members. The discussion was recorded on the Blackboard Collaborate Ultra and transcribed for purposes of data collection (the transcription included both the discussion and the chatbox comments). This facilitated classification of the collected material for subsequent analysis and interpretation. As a conclusion, it should be noted that the participating instructors generally expressed that they should not be held accountable for addressing cyberplagiarism and required broader institutional support to that end. They also expressed their commitment to counteract this problem and insisted that the academic community make a greater effort to raise awareness among students about the severity and consequences of such academic misconduct.